CHINA'S FOREIGN POLICY SHIFT FROM BELT AND ROAD INITIATIVE TO GLOBAL DEVELOPMENT INITIATIVE: IMPACTS ON MARITIME GEOPOLITICS OF THE INDIAN OCEAN REGION (Margalla Papers, 2022)
China's Belt and Road Initiative (BRI) is the foreign policy strategy that has changed world politics. It has compelled states to revisit their foreign policies either in favour of BRI or countering it. BRI has created a difficult situation for international power structure and status quo states due to transitioning power from west to east and emerging geopolitical reconfiguration. However, in September 2021, President Xi Jinping announced China's Global Development Initiative (GDI) at the opening session of the UN General Assembly, which renewed debate about the impacts of China's strategy. As China has a strong foothold in the Indian Ocean region through BRI, the undertaken research is an endeavour to study the effect of shifting China's foreign policy from BRI to GDI over the maritime geopolitics of the region. This research aims at determining GDI's role in supporting UN Agenda 2030 through focused efforts on sustainable development goals in the maritime domain. It is an exploratory and qualitative research conducted through deductive reasoning to seek an explanation of the core proposition. This research has used secondary sources for determining these upshots with potential changes in the maritime geopolitics of the Indian Ocean region. Bibliography EntryKhan, Maliha Zeba, and Zohaib Altaf. 2022. "China's Foreign Policy Shift from Belt and Road Initiative to Global Development Initiative: Impacts on Maritime Geopolitics of the Indian Ocean Region." Margalla Papers 26 (2): 14-27.